Analysis of a Hybrid Generation Scheme involving Wind and Solar PV for Grid Isolated Applications - Chatterjee, Arunava; Chatterjee, Debashis (International Journal of Computer Sciences and Engineering, 2025)
Harnessing wind power using induction generators have been widely practiced throughout the world. Hybrid wind solar generation schemes are a good option in grid isolated places. This paper presents a single-phase dual stator winding induction generator combined with a strategically connected photovoltaic panel for standalone operation suitable for microgeneration. This scheme can be installed in remote and grid unreachable areas as a reliable electrical source of power. The variable reactive power requirement of the generator is provided by a single-phase inverter. The variable frequency inverter source regulates the load voltage during fluctuating loads or low wind speeds. The generated voltage is converted to DC and is also assisted by the photovoltaic panel for battery charging. A fixed frequency inverter can then be used to supply the single-phase domestic loads. Suitable simulations validate the proposed strategy backed by experimental findings on a 250W, 240V, 50Hz, 4-pole generator.